Reliability and Dominant Factors of The Indonesian Version of Social Participation in Non-Myogenic Low Back Pain Patients - Firdaus, Muhammad Rais Hasan; Komalasari, Dwi Rosella (Academic Physiotherapy Conference Proceeding, 2024)
Introduction: Low back pain (LBP) reflects pain between the lower edge of the ribs and the buttocks. LBP can affect mental well-being, quality of life, and work activities. Therefore, this study aimed to determine the reliability, validity and dominant factors of social participation in patients with non-myogenic LBP using the PSSS scale. Method: This research used an observational study with a cross-sectional and predictive approach. Used purposive sampling data collection techniques, the total sample was 55 respondents. Results: The reliability of the PSSS scale in non-myogenic LBP patients with a Cronbach alpha value = 0.982 (excellent), the ICC value shows >0.9 (very high agreement) for all items. Construct validity was <0.05 (valid) and >0.40 for all items, except item number 13 (r=0.277 or poor validity). Multiple linear regression showed no significant association between pain and range of motion to social participation (p>0.05). Conclusion: The PSSS questionnaire is reliable regarding intra-rater as a tool for measuring social participation in non-myogenic LBP patients. Pain and range of motion did not associate with social participation in patients with non-myogenic LBP.